Cervical cancer screening program based on primary DNA-HPV testing in a Brazilian city: a cost-effectiveness study protocol - Julio Cesar Teixeira; Diama Bhadra Vale; Joana Froes Bragança; Cirbia Silva Campos; Michelle Garcia Discacciati; Luiz Carlos Zeferino (BMC, 2020)
Abstract Background The causal relationship between high-risk (hr) HPV infection and precancerous lesions or cervical cancer has led to the development of strategies to increase screening performance and prevent this cancer. The increased sensitivity of DNA-HPV testing compared to cervical cytology favors DNA-HPV testing as a primary screening test. Cervical cancer screening in Brazil is opportunistic, and this cancer remains a considerable health problem with a high proportion of diagnoses in advanced stages. This paper aims to describe the design and implementation of the Cervical Cancer Screening Program with primary DNA-HPV testing (CCSP-HPV) planned for Indaiatuba City (SP), Brazil; the strategies to achieve higher population coverage; and a study protocol for cost-effectiveness analyses. Methods The CCSP-HPV was designed based on successful guidelines that replaced cervical cytology-based screening by the DNA-HPV test performed at 5-year intervals. The screening will be performed for the female population aged 25-64 years cared for by the public health system and aim to reach 80% coverage after completing the first round. The chosen DNA-HPV test detects 14 hr-HPV types and genotypes HPV-16 and 18. All women with a negative test will be reassessed after five years. Women showing a positive test for HPV-16 and/or 18 will be referred for colposcopy. Those showing the other 12 hr-HPV types will be tested by cytology, and if any abnormality is detected, they will also be referred for colposcopy. The histopathologic evaluation will be reviewed by a pathologist panel and aided by p16 immunohistochemistry. A cost-effectiveness analysis will be performed by a Markov model comparing the cost of the new program and the screening performed by conventional cytology five years prior (2011-2016). Discussion The new screening program is considered a breakthrough for public health regarding cervical cancer, which is the third leading cause of cancer death among Brazilian women. Achieving at least 80% coverage will have the possibility to change this scenario. The proposed program will provide a modern cervical cancer screening method for women, and information about cost-effectiveness will help other similar places support the decision of implementing cervical cancer screening using the DNA-HPV test.